Depiction of a sleeping couple with a snake near the leg of the man - Temples of India Project Team (Jio Institute, 2024)
The ninth oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) is difficult to decipher. It appears to depict a sleeping couple, with a snake near the leg of the man. Outside the haveli (mansion) which houses this couple, there is an armed figure that looks like a soldier or guard in uniform.